A Case Study of Egirdir Zero Waste Park for Living and Learning - Sahin, Candan Kus; Solak, Esra Bayazıt; Sava, Beyza; Onay, Busra (European Journal of Applied Sciences, 2022)
Due to increasing demand on natural and man-made sources in all areas, some of the solid materials (i.e., wood, metal, plastic) have become under pressure for effective recovery and reuse. In this sense, the use of solid waste materials in urban furniture applications has become an important need for environmentally friendly urban space design. A city park, Eğirdir Zero Waste park, has already established from selected recovered solid wastes as urban furniture elements, was evaluated in view of landscape architecture discipline. The park was found to be design in sustainability concept which offer multiple ways for users to interact with it. It looks created urban furniture and playground elements useful and safe not only for children’s but also all other user groups for living and learning concept. The park elements and decorative objects are created by and the combination of, waste wood, retailed railroad tie, old telephone posts, waste tires, metal scraps, old irrigation vessels which not only play a role of partition and guidance, but also can be useful as a background and a beautiful decoration from the aesthetical view point. It is clear advantage to use those materials in park as urban furniture, may confer sustainability identity feelings. All these elements were found to be very helpful to the knowledge, and creates interesting areas for the visitor with supplying special concept on selected solid waste concern. It looks one of the aims of built that park is to keep alive of solid wastes to users.